Debt to Equity Ratio (DER) and Firm Size Toward Firm Value : The Mediating Role of Return on Asset - Elly Lestari (PT. Publikasiku Academic Solution, 2023)
This “research delves into the critical aspects of company sustainability Debt to Equity Ratio and Firm Size and their consequential impact on company value. The focus is on scrutinizing the interplay of these elements on Firm Value through the lens of Return On Assets within Manufacturing Companies listed on the Indonesian Stock Exchange. The research encompasses manufacturing companies with Corporate Governance reports up to 2018, with a meticulous exclusion of those lacking routine publication during the observation period from 2012 to 2018. The study adopts a saturated sample approach, including all 14 eligible companies, resulting in a robust set of 98 observations. The anticipated outcomes seek to elucidate the intricate dynamics influencing Firm Value, specifically examining the roles of Debt to Equity Ratio, Firm Size, and Return On Assets. Methodologically, path analysis is the chosen tool for data examination. The findings highlight the direct impact of Debt to Equity Ratio and Firm Size on Firm Value, with an additional revelation that Firm Value is not only directly influenced but also mediated by Return On Assets, particularly in the context of Firm Size within Manufacturing Companies on the Indonesian Stock” Exchange. This research reveals a crucial discovery: Firm Value is influenced not only by the Debt to Equity Ratio and Firm Size, but also by the mediating effect of Return On Assets in Manufacturing Companies listed on the Indonesian Stock Exchange. Essentially, the complex interactions of these interconnected components provide a complete understanding of the complicated forces that determine the value of these organizations.